2023
DOI: 10.3390/molecules28072935
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of β-Cryptoxanthin on 5-Fluorouracil-Induced Cytokine Expression in Human Oral Mucosal Keratinocytes

Abstract: Oral mucositis is a typical adverse effect of chemotherapy, causing oral pain that significantly reduces the patient’s quality of life. β-cryptoxanthin (β-cry) is a carotenoid abundant in citrus fruits with antioxidant and anti-inflammatory effects. However, the β-cry effect on oral mucositis remains unclear. We investigated the effects of 5-fluorouracil (5-FU) and β-cry on human normal oral mucosal keratinocytes (hOMK). hOMK was seeded on a culture plate and cultured with 5-FU and β-cry. The cell number, mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…59,61 Studies have indicated that 5-FU induces an increase in MMP-9 expression in the oral mucosa, leading to significant apoptosis in both epithelial and connective tissues, ultimately resulting in tissue damage. 62,63 In the context of in vivo experiments, the immunofluorescence analysis revealed the expression pattern of MMP-9 in tissue cells (Figure 7C). Notably, by day 3, a noticeable decrease in the relative fluorescence intensity of MMP-9 was observed in the Col/HA-E/Alg hydrogel group, as illustrated in Figure 7D.…”
Section: Col/ha-e/alg Hydrogel Enhances Angiogenesis In the Rat Model...mentioning
confidence: 99%
“…59,61 Studies have indicated that 5-FU induces an increase in MMP-9 expression in the oral mucosa, leading to significant apoptosis in both epithelial and connective tissues, ultimately resulting in tissue damage. 62,63 In the context of in vivo experiments, the immunofluorescence analysis revealed the expression pattern of MMP-9 in tissue cells (Figure 7C). Notably, by day 3, a noticeable decrease in the relative fluorescence intensity of MMP-9 was observed in the Col/HA-E/Alg hydrogel group, as illustrated in Figure 7D.…”
Section: Col/ha-e/alg Hydrogel Enhances Angiogenesis In the Rat Model...mentioning
confidence: 99%
“…Importantly, the transcription factor NF-κB is a key component activated by TLR signaling and is known to contribute to numerous inflammatory signals, including those leading to OM [58,59]. During ulcerative mucositis, PAMPs, such as lipopolysaccharides, can interact with TLRs expressed on innate immune cells of the oral mucosa to trigger an inflammatory response [60]. In addition, release of DAMPs, such as HMGB1, from cells undergoing necrosis or oxidative stress also contributes to innate immune activation via detection by TLRs.…”
Section: Pattern Recognition Receptors and Om Developmentmentioning
confidence: 99%